Paediatric Asthma and Allergy 2019
DOI: 10.1183/13993003.congress-2019.pa942
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and respiratory symptoms among cross-country skiers in early adolescence

Abstract: Objective. To determine the prevalence of asthma and respiratory symptoms among Swedish crosscountry skiers in early adolescence in comparison to a population-based reference group of similar ages. Methods. A postal questionnaire on asthma, asthma medication, allergy, respiratory symptoms, and physical activity was distributed to Swedish competitive crosscountry skiers aged 12-15 years (n � 331) and a population-based reference group (n � 1000). e level of asthma control was measured by the Asthma Control Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This, potentially, would have increased the prevalence of respiratory symptoms, because cold dry air and mountainous environments have recently been cited as the most potent for the development of symptoms following exercise in athletes [ 53 ]. Relative to young athletic individuals in Sweden [ 23 ], our results show higher prevalence, but compared to athletes in Quebec, Canada, we observed the same prevalence of symptoms after exercise [ 50 ]. We also found the same pattern of respiratory symptoms as other research following a cold air race [ 18 , 51 ] or intense exercise [ 13 ], where cough was the most prevalent symptom compared to other symptoms (wheeze, chest tightness/trouble breathing and excessive mucus).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…This, potentially, would have increased the prevalence of respiratory symptoms, because cold dry air and mountainous environments have recently been cited as the most potent for the development of symptoms following exercise in athletes [ 53 ]. Relative to young athletic individuals in Sweden [ 23 ], our results show higher prevalence, but compared to athletes in Quebec, Canada, we observed the same prevalence of symptoms after exercise [ 50 ]. We also found the same pattern of respiratory symptoms as other research following a cold air race [ 18 , 51 ] or intense exercise [ 13 ], where cough was the most prevalent symptom compared to other symptoms (wheeze, chest tightness/trouble breathing and excessive mucus).…”
Section: Discussionmentioning
confidence: 44%
“…Some limited descriptive studies have shown that adult female athletes have significantly greater self-reported respiratory symptoms in a variety of HV sports compared to male athletes [ 21 , 22 ]; however, sex-based respiratory symptom differences have not been researched extensively. Recent evidence also indicates that prepubescent, male Nordic athletes (less than 13 years of age) have a greater self-reported wheeze than females, but this finding was related to greater training hours in males compared to females [ 23 ]. A recent field-based study did find a more severe EIB response in females than males at −15 °C [ 15 ]; however, the majority of known sex-based differences in respiratory function are based on warm weather or normal laboratory conditions [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results from this study show that endurance athletes are at increased risk of developing asthma. Results from previous studies show that asthma is a problem among swimmers, as well as cyclists, long-distance runners, and cross-country skiers [3,5,6,27,29]. Bougault et al studied the airways of 32 swimmers and 32 cold air athletes (11 speed skaters, 16 cross-country skiers, and 5 biathletes) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is characterized by chronic airway inflammation and bronchial hyperresponsiveness (BHR), which increased sensitivity to a wide variety of airway narrowing stimuli [1]. e reported prevalence varies between studies [3][4][5][6] and type of sport [4,7]. e diagnosis of asthma should be based on objective measurements, in addition to symptoms and clinical examination [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a Swedish study among skiers that used a postal questionnaire, 29% in the age group 15-19 years selfreported a physician-diagnosed asthma [2]. In another Swedish postal questionnaire study among adolescent skiers that also included control subjects, the prevalence of physician-diagnosed asthma was 23% among the skiers and 12% in the control group [3]. Beta2-agonists and inhaled corticosteroids (ICS), which are asthma medications, are often used among skiers for the treatment of respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%